2022
DOI: 10.1021/acs.inorgchem.2c00677
|View full text |Cite
|
Sign up to set email alerts
|

“Lock and Key” and “Induced-Fit” Host–Guest Models in Two Digold(I)-Based Metallotweezers

Abstract: Two different metallotweezers, each with two pyrene−imidazolylidene−gold(I) arms, were used as hosts for a series of planar aromatic guests. The metallotweezer with a dibenzoacridinebis(alkynyl) spacer (1) orients the two pyrene− imidazolylidene−gold(I) arms in a parallel disposition, with an interpanel distance of about 7 Å. The second metallotweezer (2) contains a carbazolylbis(alkynyl) spacer that directs the two pyrene panels in a diverging orientation. Determination of the association constants via 1 H NM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 54 publications
0
1
1
Order By: Relevance
“…It is noteworthy that for the TNFLU ligand, no change in the chemical shift of its signals was observed. This result is totally different from the one observed in the other two clamps synthesized previously, where a large increase in the association constant was observed, about 9933 M −1 [42]. With regard to the encapsulation of metal complexes, some authors previously showed how metallotweezers containing cationic alkynylplatinum arms displayed large association constants with several neutral and anionic guest planar metal complexes, including [Pt(CˆNˆC)(CO)] and [Au(CˆNˆC)(C≡CC 6 H 4 -OCH 3 -p)].…”
Section: Molecular Recognition: Determination Of Binding Affinitiescontrasting
confidence: 99%
See 1 more Smart Citation
“…It is noteworthy that for the TNFLU ligand, no change in the chemical shift of its signals was observed. This result is totally different from the one observed in the other two clamps synthesized previously, where a large increase in the association constant was observed, about 9933 M −1 [42]. With regard to the encapsulation of metal complexes, some authors previously showed how metallotweezers containing cationic alkynylplatinum arms displayed large association constants with several neutral and anionic guest planar metal complexes, including [Pt(CˆNˆC)(CO)] and [Au(CˆNˆC)(C≡CC 6 H 4 -OCH 3 -p)].…”
Section: Molecular Recognition: Determination Of Binding Affinitiescontrasting
confidence: 99%
“…In both cases the incorporation of the hydroxyl group to the periphery of the PAH guest produces increased in the association constant, very likely due to the stabilization produced by the hydrogen bonding interaction between the -OH group and the lone pair of the nitrogen at the pyridine linker. If we compare the binding affinities of the metallotweezer with those observed with the carbazole-connected metallotweezer [42], higher affinity is observed with the pyridine linker-based tweezer, 2, except that the rigid tweezer based on the dibenzoacridine-connected metallotweezer [42] has constants of association which are much higher than those observed in the pyridine linker-based tweezer, 2. and 6). In both cases the incorporation of the hydroxyl group to the periphery of the P guest produces increased in the association constant, very likely due to the stabiliza produced by the hydrogen bonding interaction between the -OH group and the lone of the nitrogen at the pyridine linker.…”
Section: Molecular Recognition: Determination Of Binding Affinitiesmentioning
confidence: 96%